Arrhythmias and laboratory abnormalities after an electrical accident: a single-center, retrospective study of 333 cases - Seyfrydova, Miroslava; Rokyta, Richard; Rajdl, Daniel; Huml, Michal (Clinical research in cardiology, 2023)
BACKGROUND: Even though electrical injuries are common in the emergency room, guidelines, consensus, and general recommendations for the management of these patients do not exist in Europe. Documented cases of delayed arrhythmias are rare and their connection with electrical injury has not been fully confirmed. We also use cardio-specific markers for the risk stratification of myocardial injury, but there is no significant study referring to their utility in this clinical situation. These reasons led us to retrospectively analyze all cases of electrical injuries over 23 years to determine the prevalence of cardiac arrhythmias (mainly malignant arrhythmias and delayed arrhythmias). METHODS: We retrospectively searched all patients admitted to the University Hospital in Pilsen, CZ, with a diagnosis of electric injury (ICD diagnostic code T754) from 1997 to 2020. The hospital´s information system was used to research the injury; data were drawn from patient medical records. RESULTS: We identified 333 cases of electrical injury in our hospital. Men accounted for about two-thirds, and women one-third. Children accounted for about one-third of cases. Most were low-voltage injuries (< 1000 V, 91.6%). All participants had an initial ECG, and 77.5% of patients had continuous ECG monitoring, usually lasting 24 h. Cardiac arrhythmias were noticed in 39 patients (11.7%). The most frequent arrhythmias were: ventricular fibrillation, sinus tachycardia, bradycardia and arrhythmia, atrial fibrillation, and supraventricular tachycardia. The ECG showed cardiac conduction abnormalities in 28 patients (8.1%), and ten patients (3%) had supraventricular or ventricular extrasystoles. In ten cases (3%), we found changes in ST segments and T waves on the initial ECG. Thirty-one patients (9.3%) suffered a loss of consciousness and 50 patients (15.02%) reported paresthesia. The most frequent ion disbalances were hypokalemia (18%) and hypocalcemia (3.3%). Patients with an ion disbalance had significantly more arrhythmias and newly diagnosed cardiac conduction abnormalities. Troponin levels (cTnI or hs-cTnT) were measured in 258 cases (77.48%) and found to be elevated above the 99th percentile in 19 cases (5.7%). Almost one-third of patients had burns of various degrees of seriousness, and 41 patients (12.3%) had concomitant traumatic injuries. Eleven patients underwent pre-hospital resuscitation, three died in the hospital, and another died as result of intracranial hemorrhage. CONCLUSION: All malignant arrhythmias occurred immediately after the electrical injury, delayed life-threatening arrhythmias were not observed, and no predictive factors of malignant arrhythmias were found. While elevations of cardiac troponins were observed sporadically, they did not appear helpful for risk stratification. In patients with arrhythmias, ion disbalance may be more critical. We concluded that asymptomatic, uninjured adult and pediatric patients with normal initial ECG findings do not need continuous ECG monitoring and may be discharged home. Recommendations for high-risk patients and patients with mild ECG abnormalities at admission are less obvious.
Keywords: Electrical accident; dospělí; Ion disbalance; nemoci převodního systému srdečního; Female; dítě; Atrial Fibrillation; Troponins; Adult; ženské pohlaví; Cardiac monitoring; Tachycardia, Sinus; lidé; Accidents; úrazy a nehody; Electrocardiography; elektrokardiografie; Electric Injuries; retrospektivní studie; Male; sinusová tachykardie; Cardiac Conduction System Disease; poranění elektrickým proudem; fibrilace síní; Child; mužské pohlaví; Retrospective Studies; Arrhythmia; Humans